Intelligence strategy: The evolution and co-evolution dynamics of intelligent human organizations and their interacting agents - LIANG, Thow Yick (Institutional Knowledge at Singapore Management University, 2004)
In the knowledge economy, the human minds are the most vital center of analysis. They are the complex adaptive systems capable of processing information, establishing knowledge structure, conceptualizing idea, and making decision. The intrinsic intelligence of the individual minds, as well as the organizational/ collective intelligence, drives the dynamic of all human systems. Primarily, the local self-enrichment processes of the interacting agents are autopoietic. In addition, global forces are also present in all human organizations. The global forces are constructive only if they support the elementary processes. The global forces originate from the orgmind of the organization. A complex relationship exists between the interacting agents and their systems. Traditionally, the decision-making dynamic of the human thinking systems has been dealt with in economics concepts such as the economic man that focuses on perfect rational decision, and Herbert Simon's administrative man that incorporates the idea of bounded rationality. In this study, the dynamic of an intelligent person is introduced. An intelligent person does not concentrate on optimality at all times. Instead, such a person adopts the intelligence strategy. An intelligent person is mindful and contributes continuously towards the collective intelligence of the system. The mindset of an intelligent person encompasses continual fast learning, longer-term survival, exploitation of the butterfly effect, and co-evolution with his/her system. In this respect, an intelligent person is a rather dissimilar interacting agent.